The relationship between N-terminal pro-brain natriuretic and coronary artery lesions in Kawasaki disease: A meta-analysis - Yanyan Li; Chaolong Zheng; Sisi Cheng; Limin Chu; Zhiqing Chen; Guiling Liu (PLoS ONE, 2025)
Background Regarding the value of N-terminal brain natriuretic peptide precursors in evaluating coronary artery lesions (CAL) in Kawasaki disease. Objective To conduct a meta-analysis of relevant literature and explore the value of N-terminal brain natriuretic peptide NT ProBNP in evaluating coronary artery lesions (CAL) in Kawasaki disease. Method Retrieve publicly published literature on the relationship between serum NT ProBNP concentration and coronary artery disease in Kawasaki disease from CNKI, Wanfang, VIP, China Biomedical Database, Pubmed, Embase, Cochrane Library, Web of Science, and OVID databases, as well as manually search for other resource literature. Use state14 software to evaluate the quality of the included literature, calculate the combined sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic ratio ratio, and compile a comprehensive subject working characteristic curve (SROC) to calculate the area under the curve (AUC) and 95% confidence interval. Result A total of 25 articles were included using a random effects model, with a combined sensitivity of 0.80 [95% CI (0.74, 0.85)], specificity of 0.78 [95% CI (0.75, 0.82)], positive likelihood ratio of 3.94 [95% CI (3.32, 4.69)], negative likelihood ratio of 0.23 [95% CI (0.17, 0.30)], and diagnostic ratio of 17.24 [95% CI (12.0,24.77)]. The area under the SROC curve AUC is 0.87 (0.84–0.90). When the predicted value is 1000ng/L, the combined sensitivity is 0.87 [95% CI (0.80,0.92)], and the specificity is 0.78 [95% CI (0.71,0.84)]. Subgroup analysis revealed that the diagnostic value of NT ProBNP for Kawasaki disease complicated with CAL was higher in the over 3 year old group than in the under 3 year old group. NT ProBNP had higher diagnostic value for Chinese population, but its exclusion value was lower than that of Japanese population. The sensitivity and specificity of using chemiluminescence to detect NT-ProBNP were higher than those of enzyme-linked immunosorbent assay. Conclusion NT-ProBNP has high diagnostic value for coronary artery lesions in Kawasaki disease, and has greater diagnostic value for children over 3 years old, and the use of chemiluminescence.It demonstrates superior diagnostic efficacy for the Chinese population and enhanced exclusionary power for the Japanese population.